A mulher acometida de acidente vascular cerebral: cuidados de enfermagem no processo de reabilitação - Lima, Cibelly Aliny Siqueira (2003)
Cardiovascular disease is the third most common cause of death and that which most causes disability in the population of developed countries. Currently, there is a great deficiency in services and basic facilities for a person who suffered a CVA (Cardiovascular Accident). This study has the objective of investigating the repercussions of a CVA occurrence in the daily routine of a woman and to identify the necessities expressed by a woman suffering from CVA, as also to suggest strategy guidance for releaming self-care at home. Qualitative research of case study type, with women suffering from cardiovascular accident, residents in the municipal of Sobral-CE, with communication capacity, including non-verbal, who have presented only one CVA episode and are in the process of rehabilitation. The sample was made up of five women selected from hospital reports at the "Santa Casa de Misericórdia de Sobral" Hospital. The data were collected during the months of September and October, 2002, at the women's own residences, whose instrument consisted of observation of the participant and the application of a projective technique, the Lüscher Color Test. The results were analyzed through the Content Analysis Method proposed by Bardin, (1976), using the technique of categorical analysis. From the results emerged the following categories: 1) the home and its influence in the rehabilitation process of a woman with CVA; 2) CVA as an initiating factor of changes in the life of a woman; 3) changes in self-impression and self-esteem in the life of a woman suffering from CVA; 4) CVA as an impeding factor for domestic, social and professional activities, and 5) spiritual necessities of a woman suffering from CVA. It was possible to perceive that CVA brought about significant repercussions to the new living conditions of Nikê, Afrodite, Atena, Ananke and Hebe - fictitious names attributed to the women involved in the study - during the rehabilitation process of the women. The living conditions of the women led us to believe that the initial stages of the disease may be as anguishing to the family as to the person with CVA; the uncertainty to their own future; the fear of another vascular accident and death, dependence; the feeling of troubling others, are difficult and common situations that these women face after suffering CVA. We observed that during the rehabilitation process they felt the reality of chronic disease; uncertainty, the sensation that something is wrong in their physical, emotional and social lives. Diverse emotions and unpleasant physical sensations come about, they may be influenced by biological, psychological and social variables which may alter in their dimensions, time and space, as well as, by the significance that the individual attributes to this experience, who in turn depends on life guidance, strength and necessities, which may worsen the impact of disabilities in their daily routine, determining a new direction in their process of living and being healthy.